Alinhamento do gerenciamento de projetos à estratégia da empresa: uma survey - Almeida, Norberto de Oliveira (2010)
This dissertation discuss about critical issues regarding portfolio, program and project management in the companies and need to be understood widely, going cross the project success concept, how to link project management to the company strategy and what metrics suite the companies think as important and have been using to assess the project s performance. Studies from the major world authors show a lack of consensus about these questions. In Brazil, the Benchmarking Study in Project Management of PMI s Local Chapters (2007) shows that most of the companies studied don t have a process to assess if they are reaching their expected business goals with the project management investments. The final goal of this work is to identify the good practices and to propose a basic model to align the project management to the company strategy and to assess the benefits of this link using a theorist referential and a survey regarding ways to define project success, models that enable the alignment of project management with the company strategy and what metrics suite makes possible to perceive the value of the project management at the companies. Based on the existing literature and the best practices of the major world references, questionnaires have been developed to demonstrate how the companies deal with these questions. Using a Survey, qualitative results have been collected and developed a model enabling us to make a critical analysis regarding these questions and support the project managing development in the organizations, aiming a better integration with the businesses goals of the companies and providing important information for future studies